Electron Microscopic Radioautographic Study on Mitochondrial DNA Synthesis in Adrenal Cortical Cells of Developing and Aging Mice - Tetsuji Nagata (The Scientific World Journal)
In order to study the aging changes of intramitochondrial DNA synthesis of mouse adrenal cortical cells, eight groups of developing mice, each consisting of three individuals (total 24), from fetal day 19 to postnatal newborn at days 1, 3, 9, 14, to adult at months 1, 2, and 6, were injected with 3H-thymidine, sacrificed 1 h later, and the adrenal tissues were fixed and processed for electron microscopic (EM) radioautography. On EM radioautograms obtained from each animal, the number of mitochondria and the mitochondrial labeling index labeled with 3H-thymidine showing DNA synthesis in each adrenal cortical cell, in three zones, were counted and the results in respective developing groups were compared. From the results, it was demonstrated that the numbers of mitochondria in the three zones, the zona glomerulosa, fasciculata, and reticularis, of mice at various ages increased from fetal day 19 to postnatal month 6 due to development and aging of animals, respectively, while the number of labeled mitochondria and the labeling index of intramitochondrial DNA syntheses incorporating 3H-thymidine increased from fetal day 19 to postnatal month 2, reaching the maxima, and decreased to month 6. It was shown that the activity of intramitochondrial DNA synthesis in the adrenal cortical cells in developing and aging mice changed due to aging.